Development and external validation of a post-discharge bleeding risk score in patients with acute coronary syndrome: The BleeMACS score - Raposeiras-Roubín, Sergio; Faxén, Jonas; Íñiguez-Romo, Andrés; Henriques, Jose Paulo Simao; D'Ascenzo, Fabrizio; Saucedo, Jorge; Szummer, Karolina; Jernberg, Tomas; James, Stefan K; Juanatey, José Ramón González; Wilton, Stephen B; Kikkert, Wouter J; et al. (Elsevier BV, 2018)
Accurate 1-year bleeding risk estimation after hospital discharge for acute coronary syndrome (ACS) may help clinicians guide the type and duration of antithrombotic therapy. Currently there are no predictive models for this purpose. The aim of this study was to derive and validate a simple clinical tool for bedside risk estimation of 1-year post-discharge serious bleeding in ACS patients.
Keywords: Bleeding; Acute coronary syndrome; Risk score; Percutaneous coronary intervention